Cockatoo Island: pit dewatering and wall depressurisation behind critical seawall infrastructure - Powell, CL; Hall, J (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Cockatoo Island iron ore mine located in the Kimberley of Western Australia has had a history of instability related to critical seawall infrastructure over the last 15 years. This is in part due to the challenging setting of excavating an open pit directly adjacent to the sea. Seawall infrastructure has been constructed over thick very soft marine sediments to enable mining to progress below sea level over the years. Following suspension of mining in 2016 the dewatering pumps were decommissioned and the pit was allowed to flood. Planned resumption of mining in 2017 required that the pit be dewatered and then cut-back and deepened. A critical factor in the planned resumption of mining was the impact of water and pore pressure on the stability of the pit slope during initial pit lake dewatering and then subsequent mine development. The earthen seawall structure is founded on 20 m of very soft coralline sediments and forms the crest of the hanging wall of the pit. The pit slope is formed in these sediments and underlying extremely weak saprolite. The pit lake had essentially recovered to sea level and the pit wall sediments were fully saturated. A carefully reasoned approach was required to dewater the pit (and depressurise the pit walls) to prevent failure of the slope and destabilisation of the seawall. An engineered approach was developed by the mining company’s geotechnical engineer in conjunction with a hydrogeological consultant to develop a practical hydro-geotechnical solution and implement a successful pit wall depressurisationscheme. This involved iterative numerical geotechnical slope stability modelling and groundwater modelling using data from several vertically stacked vibrating wire piezometers (VWP) to calibrate the models. Initial calibration was against longer-term (pseudo-steady state) data from the period of pit flooding and then against transient pore pressure responses as dewatering of the pit lake commenced. Calibrated models were then used to predict pore pressures and slope stability for various pit development scenarios assuming both natural pit wall drainage (seepage flow to pit faces) and enhanced drainage using sand drains. A life-of-mine pit development and pit wall depressurisationplan was developed that included pit lake dewatering and detailed monitoring of piezometers and slope performance (automated prism monitoring and slope radar surveillance) to provide ongoing validation and calibration of the pore pressure and slope stability models and to ensure that these remained within acceptable limits. The adopted approach resulted in successful controlled depressurisation and stable pit slopes. Unfortunately, despite the dewatering scheme being implemented successfully, other factors resulted in the project remaining in care and maintenance. The pit has since been allowed to flood.
Keywords: open pit; slope stability; dewatering; depressurisation; seawall